The border ebook A novel. - Winslow, Don (Power of the Dog, 2019)
ONE OF THE MOST ACCLAIMED BOOKS OF THE YEAR Contains an excerpt from Don Winslow's explosive new novel, City on Fire! NAMED A BEST BOOK OF THE YEAR BY Washington Post • NPR • Financial Times • The Guardian • Booklist • New Statesman • Daily Telegraph • Irish Times • Dallas Morning News • Sunday Times • New York Post "A big, sprawling, ultimately stunning crime tableau." – Janet Maslin, New York Times "You can't ask for more emotionally moving entertainment." – Stephen King "One of the best thriller writers on the planet." – Esquire The explosive, highly anticipated conclusion to the epic Cartel trilogy from the New York Times bestselling author of The Force What do you do when there are no borders? When the lines you thought existed simply vanish? How do you plant your feet to make a stand when you no longer know what side you're on? The war has come home. For over forty years, Art Keller has been on the front lines of America's longest conflict: The War on Drugs. His obsession to defeat the world's most powerful, wealthy, and lethal kingpin?the godfather of the Sinaloa Cartel, Adán Barrera?has left him bloody and scarred, cost him the people he loves, even taken a piece of his soul. Now Keller is elevated to the highest ranks of the DEA, only to find that in destroying one monster he has created thirty more that are wreaking even more chaos and suffering in his beloved Mexico. But not just there. Barrera's final legacy is the heroin epidemic scourging America. Throwing himself into the gap to stem the deadly flow, Keller finds himself surrounded by enemies?men who want to kill him, politicians who want to destroy him, and worse, the unimaginable?an incoming administration that's in bed with the very drug traffickers that Keller is trying to bring down. Art Keller is at war with not only the cartels, but with his own government. And the long fight has taught him more than he ever imagined. Now, he learns the final lesson?there are no borders. In a story that moves from deserts of Mexico to Wall Street, from the slums of Guatemala to the marbled corridors of Washington, D.C., Winslow follows a new generation of narcos, the cops who fight them, street traffickers, addicts, politicians, money-launderers, real-estate moguls, and mere children fleeing the violence for the chance of a life in a new country. A shattering tale of vengeance, violence, corruption and justice, this last novel in Don Winslow's magnificent, award-winning, internationally bestselling trilogy is packed with unforgettable, drawn-from-the-headlines scenes. Shocking in its brutality, raw in its humanity, The Border is an unflinching portrait of modern America, a story of—and for—our time.